2013
DOI: 10.1371/journal.pone.0058719
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Elemene Blocks Epithelial-Mesenchymal Transition in Human Breast Cancer Cell Line MCF-7 through Smad3-Mediated Down-Regulation of Nuclear Transcription Factors

Abstract: Epithelial-mesenchymal transition (EMT) is the first step required for breast cancer to initiate metastasis. However, the potential of drugs to block and reverse the EMT process are not well explored. In the present study, we investigated the inhibitory effect of beta-elemene (ELE), an active component of a natural plant-derived anti-neoplastic agent in an established EMT model mediated by transforming growth factor-beta1 (TGF-β1). We found that ELE (40 µg/ml ) blocked the TGF-β1-induced phenotypic transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 50 publications
(45 reference statements)
2
34
0
Order By: Relevance
“…Many transcriptional repressors including Snail and Twist play important role in role in TGF-β1 induced EMT [30]. Further we assessed the levels of Snail and Twist in RT-PCR studies, which were significantly elevated after irradiation and this effect was reversed by halofuginone.…”
Section: Discussionmentioning
confidence: 99%
“…Many transcriptional repressors including Snail and Twist play important role in role in TGF-β1 induced EMT [30]. Further we assessed the levels of Snail and Twist in RT-PCR studies, which were significantly elevated after irradiation and this effect was reversed by halofuginone.…”
Section: Discussionmentioning
confidence: 99%
“…TGF‐β is an important inducer of EMT in cancer progression. Many papers have reported that TGF‐β could induce EMT in the MCF‐7 cells (Zhang et al, ; Walsh and Damjanovski, ). In our experiment, MCF‐7 cells were treated with TGF‐β1 at different concentrations (0, 5, or 10 ng/ml) for 48 h followed by Western blot analysis for different mesenchymal markers.…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that β-elemene significantly suppresses breast cancer cells growth and proliferation [15,16], β-elemene has a wide range of applications in traditional medicine, it has been studied as an agent capable of reversing resistance to chemotherapy [17,18]. Previous Chinese publication has shown that by up-regulating the expression of c-Cbl and Cbl-b, which leads to inhibition of PI3K/Akt signaling and down-regulation of Pgp expression [19].…”
Section: Discussionmentioning
confidence: 99%